Lubrication of asymmetric rollers considering viscosity as function of mean temperature - Lanka, Swetha; Sajja, Venkata Subrahmanyam; Prasad, Dhaneshwar (Zielona Góra: Uniwersytet Zielonogórski)
A theoretical analysis of an asymmetric roller bearing system with cavitation that is hydro-dynamically lightly loaded and lubricated by a thin, incompressible fluid is presented. The lubricant adheres to the non-Newtonian Bingham plastic fluid concept, in which the viscosity of the fluid should change depending on the mean film temperature. The continuity and momentum equations, which regulate fluid flow, are first solved analytically and then numerically using MATLAB.
Keywords: non-Newtonian; Bingham plastic; hydrodynamic lubrication; incompressible; viscosity